Fibroblast Growth Factor 21 Modulates Microglial Polarization That Attenuates Neurodegeneration in Mice and Cellular Models of Parkinson's Disease - Yang, Changwei; Wang, Wuqiong; Deng, Pengxi; Li, Chen; Zhao, Liangcai; Gao, Hongchang (Frontiers in Aging Neuroscience, 2021)
Microglial polarization and the subsequent neuroinflammatory response were identified as key contributors to the progress of Parkinson's disease (PD). Researchers have shown that fibroblast growth factor 21 (FGF21) plays multiple biological functions, including anti-inflammation and neuroprotection. However, the knowledge of FGF21 on microglial polarization in PD in vivo is far from completion. In this study, both in vivo and in vitro models were used to investigate whether FGF21 enhances the brain function by modulating microglial polarization in PD. The protective effects of FGF21 in vivo were conducted using 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-induced PD mice model alongside intraperitoneally received FGF21. A behavioral test battery and tyrosine hydroxylase (TH) immunohistochemistry were conducted to evaluate the neuronal function and nigrostriatal tract integrity. Immunofluorescence assay and Western blot were used to examine M1/M2 microglial polarization. Then, a microglia-neuron co-culture system was adopted in vitro to identify the underlying molecular mechanisms of FGF21. The results showed that FGF21 significantly alleviated motor and cognitive impairment in mice with PD. FGF21 also protected TH-positive neuron cells in the striatum and midbrain. Mechanistically, FGF21 suppressed M1 microglial polarization and the subsequent mRNA expression of pro-inflammatory factors while promoting M2 microglial polarization with increasing anti-inflammatory factors in mice with PD. Furthermore, sirtuin 1 (SIRT1) and the nuclear factor-kappa B (NF-κB) pathway were involved in the FGF21-induced M2 microglial polarization. Conversely, SIRT1 inhibitor EX527 significantly prevented both the FGF21-induced SIRT1 expression and M2 microglial polarization. Moreover, FGF21 pretreatment of microglia significantly prevented neuronal cell apoptosis in a microglia-neuron co-culture system. In conclusion, our data demonstrate that FGF21 exerted its protective effects in the pathology of PD through SIRT1/NF-κB pathway-mediated microglial polarization. Given the safety record of human clinical trials, FGF21 could be a promising therapy for clinical trials to ameliorate motor and nonmotor deficits in patients with PD.